Research of Possible Synthesis of Alkyd-Styrene Resins (Chemical and Structure Modification of Polymers, 2015)
K. I. VINHLINSKAYA,1 N. R. PROKOPCHUK,2 and A. L. SHUTOVA31PhD Student, Junior Scientific Researcher (BSTU); 2Corresponding Member of Belarusian National Academy of Sciences, Doctor of Chemical Sciences, Professor, Head of Department (BSTU); 3Candidate of Technical Sciences, Assistant professor (BSTU), Belarusian State Technological University, 13a Sverdlova Str., Minsk, 220006, Belarus, E-mail: VPSh_bstu@mail.ru, prok_nr@mail. by, a.l.shutova@mail.ruAbstract ... 61 6.1 Introduction ... 62 6.2 Experimental Part ... 63 6.3 Conclusion ... 75 Keywords ... 75 References ... 76ABSTRACTThis chapter covers possible methods of synthesis of alkyd-styrene resins, formulations and areas of application this film-formers in paint production. The article summarizes the main regularities that can help to get in the future alkyd-styrene resins of home production. Possibility of productionalkyd-styrene resins at the chemical companies opens wide prospects for creation quick and naturally drying paint materials, which will reduce the dependence on imports, provide energy savings and correspondingly increase the competitive ability of products of companies by cheapening of coatings preparation processes.